Impact of Boehmite and Gibbsite on the supercapacitor performances of polypyrrole: γ-AlO(OH)/PPy/CF and γ-Al(OH)3/PPy/CF flexible and wearable nanocomposites - Arvas, Melih Besir; Yaylagul, Sultan; Uzbicen, Kardelen; Kocyigit, Nilufer; Yagci, Ozlem (ELSEVIER SCIENCE SA, 2025)
Supercapacitors (SCs) are distinguished by their remarkable longevity and high power density. Additionally, its partnership with high-energy-density devices has benefits including the development of hybrid energy storage for electric vehicles and renewable energy systems. In this study, aluminum oxide-doped PPy/CF electrodes were synthesised by the hydrothermal method, which consisted of PPy/CF (E1), Boehmite doped PPy/CF (E2) and Gibbsite doped PPy/CF (E3) electrodes. The optimum electrodes were identified by experimenting with various boehmite and gibbsite dopant percentages and selecting the concentration that performed the best. The super- capacitor performances of the E1 electrodes doped with both bohmite and gibbsite electrodes were investigated through the application of cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and galvanostatic charge discharge (GCD) analyses. The morphological and crystal structural characteristics of these electrodes were investigated utilising scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. Raman and Fourier Transform Infrared spectroscopy (FT-IR) spectroscopy were also used to determine the structural parameters. The specific capacitances obtained from GCD measurements were found to be 917.9 F/g for 60% boehmite-doped PPy/CF (60-E2) and 774.3 F/g for 20% gibbsite-doped PPy/CF (20-E3) in PVA/H2SO4 (10 wt% PVA-0.5M H2SO4) gelled electrolyte. In symmetric supercapacitor measurements, the capacitance retention value was found to be 94.7% after 5000 cycles. The specific energy (E), and specific power (P) were found to be 56.5 Wh.kg-1 , and 2410.7 W.kg-1 , respectively.
Keywords: Boehmite; Gibbsite; Polypyrrole; Hydrothermal; Supercapacitor; Flexible; Wearable; VANADIUM-OXIDE; RAMAN-SPECTRA; ELECTRODE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering